2020
DOI: 10.1136/jnnp-2020-324837
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome and COVID-19: an observational multicentre study from two Italian hotspot regions

Abstract: ObjectiveSingle cases and small series of Guillain-Barré syndrome (GBS) have been reported during the SARS-CoV-2 outbreak worldwide. We evaluated incidence and clinical features of GBS in a cohort of patients from two regions of northern Italy with the highest number of patients with COVID-19.MethodsGBS cases diagnosed in 12 referral hospitals from Lombardy and Veneto in March and April 2020 were retrospectively collected. As a control population, GBS diagnosed in March and April 2019 in the same hospitals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
236
8
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(282 citation statements)
references
References 33 publications
14
236
8
4
Order By: Relevance
“…Within our limited case series, we observed that two out of three GBS patients developed axonal forms of the disease, contrary to what was reported by Filosto et al (25), who instead reported a higher prevalence of COVID-related demyelinating forms of GBS in a broader case series. However, data from the literature are still too preliminary to understand whether the clinical and prognostic profile of GBS or myelitis related to SARS-CoV-2 infection may present peculiar features.…”
Section: Discussioncontrasting
confidence: 99%
“…Within our limited case series, we observed that two out of three GBS patients developed axonal forms of the disease, contrary to what was reported by Filosto et al (25), who instead reported a higher prevalence of COVID-related demyelinating forms of GBS in a broader case series. However, data from the literature are still too preliminary to understand whether the clinical and prognostic profile of GBS or myelitis related to SARS-CoV-2 infection may present peculiar features.…”
Section: Discussioncontrasting
confidence: 99%
“…Does a sensory or autonomic neuropathy develop following the acute illness? In addition, there is also increased incidence of acute motor and sensory axonal neuropathy (AMSAN) and acute demyelinating inflammatory demyelinating polyneuropathy (AIDP) associated with COVID-19, both of which may have autonomic dysfunction as a component [ 18 , 19 ]. Long-COVID POTS may also represent a version of acute pan-dysautonomia which is typically post-infectious autonomic neuropathy similar to AIDP and AMSAN.…”
Section: Research Opportunities To Understand Long-covid Potsmentioning
confidence: 99%
“…Notably, several case series already conveyed a rapid sequence and even significant overlap of COVID-19 pneumonia and GBS [ 4 6 ]. We also observed such a rapid temporal sequence in three patients consecutively treated in our department between October 2020 and January 2021:…”
mentioning
confidence: 99%